Методи збору на характеристики вхідних даних системи класифікації типу фізичної активності людини - Воронін, Б. С. (ХНУРЕ, 2023)
Nowadays more and more people are becoming interested in sports and performing an active lifestyle, and many of them use various apps to track their progress, achievements, and physical health. The increasingly common features of these apps are subsystems for automatic tracking of physical activities with the recording of results according to the type of activity, for the purpose of analyzing and documenting the user's physical achievements.